Simulations on detection efficiency of CLYC (Ce) detector. (1st January 2023) - Biao, Zhang; Jinjia, Cao; Shuang, Lin; Yingming, Song
Abstract: CLYC (Ce) crystal is a new type of inorganic scintillator with excellent performance, which can realize neutron and gamma dual mode measurement. CLYC (Ce) detector is widely used in national defense, homeland security, nuclear imaging, environmental monitoring, nuclear medicine and other fields. The detection efficiency of the detector is an important index in the design and development of the detector. The detection model of CLYC (Ce) detector is established by using Geant4 program based on Monte Carlo method, and the factors affecting the detection efficiency of detector are studied. The results show that: the detection efficiency is related to the shape and size of crystal section. The detection efficiency of rectangular section is lower than that of circular and square section, and the larger the crystal radial size and length, the higher the detection efficiency. The detection efficiency of CLYC (Ce) detector is related to the energy of rays: the higher the energy of neutrons and gamma rays are, the lower the detection efficiency is. It indicates that the crystal responds better to thermal neutrons and low-energy gamma rays. At the same time, if the radiation source is emanative, the smaller the distance between the radiation source and the detector, the higher the detection efficiency of the scintillator.